Survei Pengaruh Intelegensi Pada Proses Pembelajaran Peserta Didik di SMAN 13 Surabaya - Khoirun Nisak Nurul Febrianti; Fina Alfianita; Aradhana Maheswara; Muhammad Akmal Ahsanul Haq; Abdullah Bahtiar Giovanny (Journal Innovation In Education, 2025)
This research aims to analyze the influence of intelligence on the learning process among students. The background to this research is driven by the importance of understanding how students’ intelligence levels can influence their ability to receive and process learning material. This research uses quantitative methods with a survey design to collect data from 35 students in one middle school. The instruments used in this research were filling out questionnaires and interviews with teachers. The research results show that there is a significant positive influence between the level of intelligence and student learning outcomes. The higher the level of intelligence, the better the understanding and skills students gain in the learning process. The discussion shows that intelligence can increase cognitive capacity and problem-solving abilities, which are important in learning. These findings provide implications for the development of teaching methods that can be adjusted to students’ intelligence levels to maximize learning outcomes. This research suggests the need for teachers to use a variety of teaching methods, such as visual, audio, and kinesthetic, to suit students’ needs.